PROBLEM BASED LEARNING (PBL) – QR-CODE DALAM PENINGKATAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK - Nurul Farida; Hasanudin Hasanudin; Nurain Suryadinata (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
The purpose of this research is to improve students mathematics learning outcome through Problem Based Learning (PBL) with QR-Code on MIPA class grade X SMA Negeri 1 Kotagajah (Senior High School in Kotagajah). This research is an Action Research Class. The subject of this research is 36 Students. This research is cyclus research with Kemmis and Mc Taggart Models consisting of: (1) planning; (2) implementation; (3 observation; and (4) reflection. Data collection technique is using in this research is tes. Based on the research result, then obtained the conclusion is Problem Based Learning with QR-code can improve students mathematics learning outcome on MIPA Class grade X SMA Negeri 1 Kotagajah. This matter showed a percentage value on the first cyclus is 47,22% and increase on the second cyclus to be 63,89%.